Prarancangan Pabrik Fenol dari Kumen Hidroperoksida dan Katalis Asam Sulfat dengan Proses Dekomposisi Kumen Hidroperoksida Kapasitas 50.000 Ton/Tahun - Astuti, Wahyu Puji, Tri Widayatno,S.T., MS.c., Ph.D, Hamid Abdillah, S.T., M.T (2015)
Phenol is an intermediate product used as raw material Other products include:phenolic resin,epoxy resin(bisphenol-A), adipic acidetc.Phenol plant is planned with a capacity of 50,000 tons/year on 2018 and will be established in Gresik,East Java with a land area 18,930 m2. The process of making phenol made by reacting kumen for 925.9381 kg/h,and the reactor operates at a temperature of 65 0C and pressure 2 atm.The reaction in the reactor is exothermic.The main byproducts of this process is as much acetone 3,895.3363 kg/hour.Utility support the process includes the provision of water by 11,652.1105 kg/h obtained from Brantas river,steam demand as much 6,972.5602 kg/hour,demand for electricity amounted to 476.3512 kW with fuel Solar. Plant is planned to operate for 330 days per year with a number of employees 198 people,a fixed capital of Rp.330,403,840,625.93 per year. Working capital of Rp. 405,506,006,142.77 per year.After taxes profits reached Rp. 86,388,563,684.26 per year.ROI before taxes amounted to 37.49% and after tax of 26.24%.POT pretax 2.11 years and after tax of 2.77 years.BEP amounted to 55.1%.SDP amounting to 40.76%.DCF amounted to 37.8%.Based on the consideration that the ROI,POT,BEP,SDP and DCF for moderate-risk plant meets calculation then the standard phenol plant is feasible to set up.